Role of overlying and underlying limestones in the natural hydraulic fracturing of shale sections: The case of marine–continental transitional facies in the Southern North China Basin. (November 2021) - Huo, Zhipeng; Gao, Jianbo; Zhang, Jinchuan; Zhang, Dong; Liang, Yutao
Abstract: A few limestone layers usually underlie and/or overlie the shale layers/sections in marine facies, especially in marine–continental transitional facies (MCTF). The role of limestones in the natural hydraulic fracturing of shale sections will help in selecting the fracturing location, improving the stimulation power, and clarifying fracture propagation law to product more shale oil and gas. Taking an MCTF in the Southern North China Basin as an example, the differences in natural fractures and mechanical properties between limestones and shales were compared to examine the role of limestone in hydraulic fracturing. Our analyses show that shales developed more non-tectonic fractures than limestones, usually interconnected with tectonic fractures to form a fracture network. Limestones generally have a higher Young's modulus, compressive strength, in situ stress, and fracturing pressure and a more difficult fracture initiation than shales and sandstones. Overlying and underlying limestones with less fractures and higher mechanical properties can act as an effective barrier bed, which prevents induced fractures originating from the shale sections from penetrating their mechanical interfaces into the adjacent limestone sections. This action maintains a high stimulation power in the shale sections to form a complicated induced fracture network. Highlights: Limestones develop fewer non-tectonic fractures than shales. Limestones have greater Young's modulus, compressive strength, in situ stress, and fracturing pressure than shales. Limestone floors and roofs can act as fracturing barrier beds for shale sections.